2012
DOI: 10.1016/j.expneurol.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Protection from diabetes-induced peripheral sensory neuropathy — A role for elevated glyoxalase I?

Abstract: Diabetic neuropathy is a common complication of diabetes mellitus with over half of all patients developing neuropathy symptoms due to sensory nerve damage. Diabetes-induced hyperglycemia leads to the accelerated production of advanced glycation end products (AGEs) that alter proteins, thereby leading to neuronal dysfunction. The glyoxalase enzyme system, specifically glyoxalase I (GLO1), is responsible for detoxifying precursors of AGEs, such as methylglyoxal and other reactive dicarbonyls. The purpose of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 38 publications
1
38
1
Order By: Relevance
“…In the present study, before the appearance of functional impairments in the neuronal tissue of 24-week-old Goto-Kakizaki rats, reduced Glo1 activity was found in the brain, spinal cord and sciatic nerve. Other recent studies have characterised GLO1 expression in the peripheral nervous system in different murine strains and have shown that reduced GLO1 expression in a streptozotocin-induced hyperglycaemia model may lead to symptoms of diabetic neuropathy [43,44]. However, in our study, GLO1 expression at the gene level was not significantly altered (data not shown), even though the activity was significantly reduced.…”
Section: Discussioncontrasting
confidence: 69%
“…In the present study, before the appearance of functional impairments in the neuronal tissue of 24-week-old Goto-Kakizaki rats, reduced Glo1 activity was found in the brain, spinal cord and sciatic nerve. Other recent studies have characterised GLO1 expression in the peripheral nervous system in different murine strains and have shown that reduced GLO1 expression in a streptozotocin-induced hyperglycaemia model may lead to symptoms of diabetic neuropathy [43,44]. However, in our study, GLO1 expression at the gene level was not significantly altered (data not shown), even though the activity was significantly reduced.…”
Section: Discussioncontrasting
confidence: 69%
“…Oxidative stress and an increased production of reactive carbonyl compounds such as methylglyoxal are prominent factors leading to the development of diabetic neuropathy and other diabetic complications (45)(46)(47). Methylglyoxal, oxidants, and electrophilic agents formed during oxidative stress all stimulate TRPA1 (14, 16 -18), and earlier studies have demonstrated that inhibition of TRPA1 reduces or prevents both the loss of intraepidermal nerve fibers and the behavioral manifestations of STZ-induced diabetic neuropathy in the rat (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Glyoxalase activity may also be a potential biomarker for susceptibility to DPN. BALB/cByJ mouse express a 10-fold greater level of glyoxalase 1 than BALB/cJ mice and were resistant to developing an insensate neuropathy and loss of intraepidermal nerve fibers compared with the diabetic BALB/cJ mice (Jack et al, 2012).…”
Section: Blocking Advanced Glycation End-product Formation and Activamentioning
confidence: 94%
“…Although the underlying origin of the antigen was not identified, these data suggest that elevated Hsp70 antibody levels may serve as a positive biomarker for patients less prone to developing diabetic complications (Gruden et al, 2009). It may be worthwhile to determine whether a relationship exists between Hsp70 antibody levels and the level of glyoxalase 1 expression (Jack et al, 2012) as a predictive biomarker pair for the development of DPN in humans (Rabbani and Thornalley, 2011).…”
Section: Heat-shock Protein Expression and Dpn-an Impaired Defense Agmentioning
confidence: 99%